2020
DOI: 10.1007/s40264-020-00913-8
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Adverse Drug Reactions of Metformin: A Longitudinal Survey Study

Abstract: Introduction In general, women more often experience metformin-associated adverse drug reactions (ADRs) than men. Objectives We aimed to assess whether sex differences in reported ADRs for metformin are observed at different times after initiation, and to explore their concurrence with sex differences in the dose of metformin over time. This may guide future studies in assessing the involved mechanisms of sex differences in metformin-associated ADRs and may guide sex-specific management of ADRs in clinical pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 24 publications
3
45
0
Order By: Relevance
“…Endogenous PCSK9 levels ( p = 0.005), total cholesterol ( p < 0.001), HDL ( p = 0.001), and LDL ( p = 0.001), circulating leptin ( p = 0.038) were higher in female ( Table 1 ). Women were less treated with metformin ( p = 0.044), in line with the literature reporting a higher risk of adverse drug reactions, and possible drug discontinuation, with metformin in women (de Vries et al, 2020 ) and were more frequently treated with β-blockers ( p = 0.028), consistently with a recent cohort study (Walli-Attaei et al, 2020 ). Male had higher executive function, short-term memory, and praxic and mental representation skills, as reflected by TMT-A z-score ( p = 0.047), FDS z-score ( p = 0.005), and CDT z-score (0.016) ( Table 1 ).…”
Section: Resultssupporting
confidence: 86%
“…Endogenous PCSK9 levels ( p = 0.005), total cholesterol ( p < 0.001), HDL ( p = 0.001), and LDL ( p = 0.001), circulating leptin ( p = 0.038) were higher in female ( Table 1 ). Women were less treated with metformin ( p = 0.044), in line with the literature reporting a higher risk of adverse drug reactions, and possible drug discontinuation, with metformin in women (de Vries et al, 2020 ) and were more frequently treated with β-blockers ( p = 0.028), consistently with a recent cohort study (Walli-Attaei et al, 2020 ). Male had higher executive function, short-term memory, and praxic and mental representation skills, as reflected by TMT-A z-score ( p = 0.047), FDS z-score ( p = 0.005), and CDT z-score (0.016) ( Table 1 ).…”
Section: Resultssupporting
confidence: 86%
“…Gastrointestinal complaints such as diarrhea, nausea, and abdominal discomfort symptoms were common in metformin which is the first choice for diabetes with the highest volume of prescriptions. In a recent study using Dutch Pharmacovigilance data, female metformin users reported more common gastrointestinal side effects than men, with the greatest difference in nausea reporting rates (8.1% vs. 23.5%) 14 . GLP1-RA is another class strongly associated with the risk of gastrointestinal events, but whether it is gender-dependent is unknown 19 .…”
Section: Discussionmentioning
confidence: 98%
“…Regarding antidiabetic drugs, studies on the gender difference in AEs are rare, and even in clinical trials, the impact of gender was not usually assessed. Meanwhile, unfavorable results for women such as a more adverse cardiovascular disease risk profile, a higher likelihood of failing treatment goals, and more reported AEs after metformin treatment, than men, were occasionally demonstrated 11 14 . While two studies encompass the entire range of drugs to assess gender differences in AE reporting, they were not focused on antidiabetic class 7 , 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Aspirin and metformin are commonly used synthetic antiaging drugs [ 13 , 14 ], but these drugs also have significant side effects. Aspirin causes antiplatelet aggregation, and long-term use can easily cause bleeding, and patients taking metformin will have diarrhea, nausea, abdominal discomfort, and other adverse reactions [ 15 , 16 ]. The discovery and development of antiaging drugs is difficult, and the progress is slow.…”
Section: Introductionmentioning
confidence: 99%